Poverty in Golden Fishing: A Regulatory Impact Assessment of Fishermen Poverty in Indonesia - La Sugi (Indonesian Association for Public Administration, 2023)
An area's wealth of natural resources can bring prosperity to its people. However, this is not the case with the fishermen in the Maluku Tengah Regency, Maluku, Indonesia, who live in the Golden Fishing area. For nearly 20 years, fishermen in this district have lived below the poverty line. In this study, RIA will be used to evaluate policies from the central government level to the district government level. The goal is to add to the repertoire of knowledge in the study of public policy and see the causes of this issue and alternative solutions. This field research uses a qualitative approach with a Regulatory Impact Assessment (RIA) analytical instrument. This study found that the government needed adequate strategies and designs to get fishermen out of the poverty trap. As a result, the government needs help to make quality policies. So that the strategic plan of the Fisheries Service of the Maluku Tengah Regency, which should be the spearhead of fisherman poverty reduction policies, becomes the most dominant inhibiting factor in creating fishermen's welfare. The proof is that many programs in the strategic plan do not favor fishermen. So the Fisheries Service of the Maluku Tengah Regency needs to evaluate the strategic plan as a whole so that it can have a positive impact on fishermen.